Conceptual Design of Collimator at Boron Neutron Capture Therapy Facility with 30 MeV Cyclotron and Target 9Be as Neutron Generator Using Monte Carlo N-Particle Extended Simulator - Prayoga Isyan; Andang Widi Harto; Yohannes Sardjono (Indonesian Journal of Physics and Nuclear Applications, 2017)
The optimization of collimator has been studied which resulted epithermal neutron beam for Boron Neutron Capture Therapy (BNCT) using Monte Carlo N Particle Extended (MCNPX). Cyclotron 30 MeV and 9Be target is used as a neutron generator. The design criteria were based on recommendation from IAEA. Mcnpx calculations indicated by using 25 cm and 40 cm thickness of PbF2 as reflector and back reflector, 15 cm thickness of TiF3 as first moderator, 35 cm thickness of AlF3 as second moderator, 25 cm thickness of 60Ni as neutron filter, 2 cm thickness of Bi as gamma filter, and aperture with 20 cm of diameter size, an epithermal neutron beam with an intensity  1.21 × 109 n.cm-2.s-1, fast neutron and gamma doses per epithermal neutron of 7.04 × 10-13  Gy.cm2.n-1 and 1.61 × 10-13 Gy.cm2.n-1, minimum thermal neutron per epithermal neutron ratio of 0.043, and maximum directionality of 0.58, respectively could be produced. The results have not passed all the IAEA’s criteria in fast neutron component and directionality.